REPRESENTASI CITRA LAKI-LAKI BUDAYA SUNDA (STUDI ANALISIS SEMIOTIK CHARLES SANDERS PEIRCE DALAM SINETRON PREMAN PENSIUN) - Nanda Utaridah (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2015)
Lifting Sunda culture in this Retired Sinetron Freeman become fascination a look on because of setting, dialectal of Ianguage, and comedy situation in its story jell with atmosphere of kesundaan and town of Bandung. Retired Freeman narrate life of group